2021
DOI: 10.1038/s42003-021-01929-1
|View full text |Cite
|
Sign up to set email alerts
|

A genome-scale CRISPR Cas9 dropout screen identifies synthetically lethal targets in SRC-3 inhibited cancer cells

Abstract: Steroid receptor coactivator 3 (SRC-3/NCoA3/AIB1), is a key regulator of gene transcription and it plays a central role in breast cancer (BC) tumorigenesis, making it a potential therapeutic target. Beyond its function as an important regulator of estrogen receptor transcriptional activity, SRC-3 also functions as a coactivator for a wide range of other transcription factors, suggesting SRC-3 inhibition can be beneficial in hormone-independent cancers as well. The recent discovery of a potent SRC-3 small molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…In vivo testing of the SRC-3 inhibitor revealed a slight decrease in tumor growth in all genotypes, although the single agent treatment was not sufficient for significant tumor regression. We used the SRC-3 inhibitor SI-2 in our studies; however, SI-12 is an improved version that was recently published and may have more efficacy in these models [40]. The in vivo experiments showed significant but partial tumor growth reduction following CDK9 inhibition in wildtype and ER mutant models.…”
Section: Er Rime Countsmentioning
confidence: 99%
“…In vivo testing of the SRC-3 inhibitor revealed a slight decrease in tumor growth in all genotypes, although the single agent treatment was not sufficient for significant tumor regression. We used the SRC-3 inhibitor SI-2 in our studies; however, SI-12 is an improved version that was recently published and may have more efficacy in these models [40]. The in vivo experiments showed significant but partial tumor growth reduction following CDK9 inhibition in wildtype and ER mutant models.…”
Section: Er Rime Countsmentioning
confidence: 99%
“…For this study, our aim was to identify new factors that play a role in ligand-dependent and -independent signaling of ERa, and in the responses of breast cancer to endocrine therapy with tamoxifen or ICI. Genetic screens using the clustered, regularly interspaced, short palindromic repeats (CRISPR) system using the RNA-guided endonuclease Cas9 represent powerful tools for the discovery of essential genes, drug targets, or biomarkers of drug resistance (29)(30)(31)(32). Screens with the tamoxifen-sensitive breast cancer cell lines MCF7 and T47D identified gene deletions, such as that of CSK, mediating estrogenindependent growth (32).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of ARID1A and components of the SWI/SNF complex were identified as prerequisites for the response of MCF7 cells to 4-hydroxytamoxifen (4-OHT), the major active metabolite of tamoxifen, and to ICI ( 30 ). A chemogenetic screen using an inhibitor of the ERα coactivator SRC-3 in MCF7 cells identified several new potential drug targets ( 29 ). Moreover, a specific CRISPR/Cas9 screen targeting CTCF binding sites in the vicinity of ERα-bound enhancers identified ERα target genes such as PREX1 as being vital for ERα function ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic lethal screens support the discovery of novel cancer drug targets 1 . In a recent issue of Communications Biology , Gilad et al 2 performed a synthetic lethal CRISPR Cas9 dropout screen in the human, estrogen receptor positive breast cancer (BC) cell line MCF-7. They aimed to identify targets that increased the sensitivity of the MCF-7 cells to the small molecule inhibitor SI-12, which targets SRC-3, an essential transcriptional cofactor of the estrogen receptor.…”
mentioning
confidence: 99%
“…The identification of novel drug targets is an important pillar in expanding the treatment options for patients with cancer. Through their screen, Gilad et al identified the olfactory receptors OR4D6 and OR5I1 , next to a number of other genes, as potential targets in patients with breast cancer 2 . Interestingly, other studies have implicated olfactory receptors (ORs) in cancer biology in general 3 , and also specifically in BC 4 , 5 .…”
mentioning
confidence: 99%